2015
DOI: 10.1097/icb.0000000000000140
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Myeloid Leukemia Diagnosed in a Patient With Uncontrolled Proliferative Diabetic Retinopathy

Abstract: Other pathologies should be excluded in diabetic patients with a rapid and severe progression in their retinopathy despite adequate metabolic control. These patients should be treated promptly and aggressively until systemic disease is stable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 7 publications
1
23
0
Order By: Relevance
“…Schmid et al 7 have reported a case of transient severe non-proliferative DR in an adolescent with type 1 diabetes and CML, which regressed later with the treatment of CML alone. Raynor et al 6 and Figueiredo et al 8 reported cases of type 2 diabetes with sudden worsening of DR to proliferative stages, which was consistent with the development of CML in these cases. The factors which may contribute to the development and rapid worsening of DR include enhanced endothelial dysfunction, vascular stasis, and retinal ischaemia due to associated anaemia.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Schmid et al 7 have reported a case of transient severe non-proliferative DR in an adolescent with type 1 diabetes and CML, which regressed later with the treatment of CML alone. Raynor et al 6 and Figueiredo et al 8 reported cases of type 2 diabetes with sudden worsening of DR to proliferative stages, which was consistent with the development of CML in these cases. The factors which may contribute to the development and rapid worsening of DR include enhanced endothelial dysfunction, vascular stasis, and retinal ischaemia due to associated anaemia.…”
Section: Discussionsupporting
confidence: 66%
“…Only a few case reports exist on proliferative retinopathy in patients with diabetes and CML. 68 , 16 A summary of cases of proliferative retinopathy in patients of CML with or without diabetes is provided in Table 2. Schmid et al 7 have reported a case of transient severe non-proliferative DR in an adolescent with type 1 diabetes and CML, which regressed later with the treatment of CML alone.…”
Section: Discussionmentioning
confidence: 99%
“…The review of the literature revealed few case reports and articles addressing effects of leukemia and imatinib that can result in glaucoma. [234567] Sharma et al attributed the leukemic infiltration and blockage of the trabecular meshwork, leading to the raised IOP. [2] Figueiredo et al attributed hyperviscosity syndrome associated with CML resulting in retinal ischemia leading to upregulation of vasoproliferative factors including vascular endothelial growth factor (VEGF) and hence, rapid progression in diabetic retinopathy (DR) and NVG.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Figueiredo et al attributed hyperviscosity syndrome associated with CML resulting in retinal ischemia leading to upregulation of vasoproliferative factors including vascular endothelial growth factor (VEGF) and hence, rapid progression in diabetic retinopathy (DR) and NVG. [5] Gulati and Saif reported a non-diabetic 62-year-old male, on imatinib (400 mg OD) for gastrointestinal stromal tumor, developed retinal neovascularization, and hemorrhage after 7 months of initiation of treatment. [6] A dose reduction to 200 mg OD resulted in resolution of hemorrhages without affecting efficacy of drug.…”
Section: Discussionmentioning
confidence: 99%
“…These potentially blinding complications are most commonly associated with chronic myeloid leukemia (CML). [6][7][8][9][10][11][12][13] It is thought that chronic leukocytosis in CML can lead to an increase in blood viscosity and retinal capillary closure, and widespread, chronic capillary closure can in turn lead to neovascularization.…”
Section: Introductionmentioning
confidence: 99%